L’enchantement de la lecture chez Alphonse Daudet ou la champignonnière de grands hommes - Lúcia Bandeira (Carnets)
The study of Alphonse Daudet’s work allows us to verify that authors used to read each other’s work; they wrote about such work and shared moments of creation and literary production activities, vastly referred to in all the authors’ adopted literary styles, reflect a common place in his literary production as well as showing a modus vivendi.